Aminoguanidine hydrazones (AGH's) as modulators of norfloxacin resistance in Staphylococcus aureus that overexpress NorA efflux pump - Dantas, Natalina; de Aquino, Thiago Mendonça; de Araújo-Júnior, João Xavier; da Silva-Júnior, Edeildo; Gomes, Ednaldo Almeida; Gomes, Antoniel Augusto Severo [UNESP]; Siqueira-Júnior, José Pinto; Mendonça Junior, Francisco Jaime Bezerra (Elsevier, 2018)
One of the promising fields for improving the effectiveness of antimicrobial agents is their combination with efflux pump inhibitors (EPIs), which besides expanding the use of existing antibiotics. The goal of this research was to evaluate a series of aminoguanidine hydrazones (AGH's, 1–19) as antibacterial agents and NorA efflux pump inhibitors in Staphylococcus aureus strain SA-1199B. Molecular modeling and docking studies were also performed in order to explain at the molecular level the interactions of the compounds with the generated NorA efflux pump model. The MICs of the antibiotic and ethidium bromide were determined by microdilution assay in absence or presence of a subinhibitory concentration of aminoguanidine hydrazones and macrophages viability was determined through MTT assay. Bioinformatic software Swiss-Model and AutoDock 4.2 were used to perform modeling and docking studies, respectively. As results, all AGH's were able to potentiate the action for the antibiotic norfloxacin, causing MIC's reduction of 16-fold and 32-fold to ethidium bromide. In the cell viability test, the concentration of 10 μg/mL showed better results than 90% and the concentration of 1000 μg/mL showed the lowest viability, reaching a maximum of 50% for the analyzed aminoguanidine hydrazones. Molecular docking studies showed that both norfloxacin and derivative 13 were recognized by the same binding site of NorA pump, suggesting a competitive mechanism. The present work demonstrated for the first time that AGH derivatives have potential to be putative inhibitors of NorA efflux pump, showing a promising activity as an antibacterial drug development.
Keywords: Aminoguanidine hydrazones; Docking; Efflux pump inhibitors; Staphylococcus aureus